An implementation framework for BYOD in a selected state-owned enterprise - Mokoena, Elliot (My University, 2020)
This study will explore the Bring Your Own Device (BYOD) phenomenon in South African State-Owned Enterprise, Transnet. The concept has become significant during the global pandemic lockdown and the resultant slowing of the economy forcing state-owned enterprises to review their cost saving measures. The objective is to identify critical factors influencing BYOD implementation with the purpose of understanding how these factors shape the actions of the information technology portfolio at Transnet. The Perceived e-Readiness Model (PERM) isadopted to identify contextual BYOD adoption factors. There are several studies conducted on the corporate adoption of BYOD, but few have investigated the phenomenon from state-owned enterprise (SOE) perspective in South Africa specifically. The study highlights the importance of technological and organisational readiness in the adoption of BYOD. Due to the complexities in cyber security, the study further highlights the importance of IT security to ensure correct adoption of BYOD as a response to continued work from home response during the Covid-19 pandemic, securing both the user’s privacy and confidentiality as well as the organisational goals of productivity.
A research report submitted in partial fulfilment of the requirements for the degree of Masters of Management (in the field of Digital Business) to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2022
Keywords: BYOD; Mobility; Work from home; UCTD; SDG-8: Decent work and economic growth